Diversidad de Tettigoniidae (Orthoptera: Ensifera) en la Huasteca de Hidalgo, México - Fernández-Azuara, Geovany de Jesús; Barrientos-Lozano, Ludivina; Zaldívar-Riverón, Alejandro; Correa-Sandoval, Alfonso; Niño-Maldonado, Santiago; Almaguer-Sierra, Pedro (Instituto de Ecología, A.C., 2018)
Four subfamilies, 17 genera and 22 species of Tettigoniidae are reported; of these, 11 are new records for the state of Hidalgo. The Shannon index showed that the study area presents a high and uniform diversity: Oak Forest (BE) H'= 2.78, Rain Forest (SM) H'= 2.23 and Mountain Cloud Forest (BMM) H'= 2.13. The subfamily Phaneropterinae showed the highest abundance (N) with 103 individuals, representing 53% of the total collected specimens (195). This subfamily also showed the highest richness (S) with 67% (14 taxa) of the total species (22) collected. The Sorensen index, modified by Bray Curtis showed that similarity in the faunal composition between the ecosystems is as follows: BE-SM (0.36), SM-BMM (0.49) and BMM-BE (0.33). The Morisita-Horn Index resulted in a similarity of 77% between BE-SM, 62% between SM-BMM and 76% between BE-BMM. Both, N and S showed a negative relationship in reference to the elevational gradient, which occurs in other insect groups.